ANALISIS VIRTUAL REALITY PADA GAME VR CRAZY BOXING DI GAME BLINK PLAYSTATION PADANG - Rini Novita; Adinda Novidia Sari, Dimas Wahyu Pratama, Reski Budiman, Fitria Marwa, Febi Rahma Yani, Wahnada, Rid (HUMANITIS: Jurnal Homaniora, Sosial dan Bisnis, 2024)
This research examines the implementation of Virtual Reality (VR) technology in the boxing game "GameBlink: Crazy Boxing Game". The main goal is to analyze the technical aspects and user experience of the VR game. The methodology used includes live testing of the game, analysis of VR features, as well as a survey of 50 players with various levels of VR experience. Results show that the game succeeds in creating an immersive boxing experience, with an average immersion score of 8.2/10. Hand motion tracking has 95% accuracy, contributing significantly to gameplay realism. Interactive 3D environments and spatial audio enhance the sense of presence, with 88% of respondents reporting high levels of presence. However, 35% of players reported discomfort after 30 minutes of play, indicating areas that need improvement.